PENGARUH MODEL PEMBELAJARAN AIR (AUDITORY INTELLECTUALLY REPETITION) TERHADAP HASIL BELAJAR KEARSIPAN SISWA KELAS X SMK HARAPAN BANGSA TAHUN 2021-2022 - Dwi Annisah Rambe; Nurjannah Nurjannah (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the effect of the AIR (Auditory Intellectually Repetition) Learning Model on Archival Learning Outcomes of Class X SMK Harapan Bangsa Tanjung Morawa in 2021-2022. This research is associative, namely research that aims to determine the effect of two or more variables. This research uses a field study approach, namely a study based on facts that occur in the object of research. The population in this study were students of class X at SMK Harapan Bangsa Tanjung Morawa, namely class X A as many as 30 students. The research sample that will be used in this research is the students of class XA at ​​SMK Harapan Bangsa Tanjung Morawa totaling 30 students. The analysis technique used is simple regression analysis and hypothesis testing. The suitability test using simple linear regression and hypothesis testing (t test) was carried out to determine the effect of the AIR (Auditory Intellectually Repetition) Learning Model on Archival Learning Outcomes of Class X SMK Harapan Bangsa Tanjung Morawa in 2021-2022. Based on the results of the research conducted, it was concluded that there was a positive influence between the AIR learning model on the learning outcomes of Class X students at SMK Harapan Bangsa Tanjung Morawa in the Academic Year Archives Subject. 2021-2022, this is evidenced by the tcount value of the AIR learning method variable of 3,231. This means that the value of tcount is greater than ttable (3.231<1.701) which indicates that the Water Learning Model has a positive effect on student learning outcomes.